PERAN MASYARAKAT DALAM PEMBANGUNAN INFRASTRUKTUR JALAN DI DESA DURIAN, KECAMATAN SUNGAI AMBAWANG, KABUPATEN KUBU RAYA - Dodi Alfaed; Arkanudin Arkanudin; Monika Maya; Siti Aminah; Marini Marini; Riyana Ramadhani Putri; Yazid Zibran (Universitas Hamzanwadi, 2024)
Infrastructure development is the government's responsibility towards the community, but in reality the infrastructure growth carried out by the government is gradual, this gives rise to unequal development in each region which has an impact on unequal road development. This research was conducted because of uneven development in Durian Village, while based on the APBDes, the priority development in the village is infrastructure. The aim of the research is to describe the roles played by the community in building roads. This research method uses a qualitative method with a descriptive analysis approach, determining informants using a purposive sampling technique consisting of 5 people. The results of research on the role of NGOs in the form of deliberation and fundraising carried out by the community are mutual cooperation, contributions and cooperation with NGOs. The role of NGOs and communities in the road construction process.